2019
DOI: 10.1093/comnet/cnz023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of semantic networks in biomedical texts

Abstract: Language is hierarchically organized: words are built into phrases, sentences, and paragraphs to represent complex ideas. A similar hierarchical structure is observed across many other biological, electronic, and transportation networks supporting complex functions. Here we ask whether the organization of language in written text displays fractal hierarchical architecture. Specifically, we test two hypotheses: (i) that the structure of the exposition in scientific research articles displays the Rentian scaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The cognitive maps arising from kinesthetic curiosity might improve their learnability, conveying information efficiently by omitting unnecessary detail [65,26,75,76]. Recent work reported that to efficiently convey information, network representations of that information should be characterized by highly connected hubs and tightly linked modules [26,77]. Hubs and modules are features of hierarchical organization exhibited by diverse signatures of kinesthetic curiosity (Figure 2).…”
Section: Efficient Search Enhances the Learnability Of Cognitive Mapsmentioning
confidence: 99%
“…The cognitive maps arising from kinesthetic curiosity might improve their learnability, conveying information efficiently by omitting unnecessary detail [65,26,75,76]. Recent work reported that to efficiently convey information, network representations of that information should be characterized by highly connected hubs and tightly linked modules [26,77]. Hubs and modules are features of hierarchical organization exhibited by diverse signatures of kinesthetic curiosity (Figure 2).…”
Section: Efficient Search Enhances the Learnability Of Cognitive Mapsmentioning
confidence: 99%
“…But beyond the networks studied thus far (only 3 out of the possible 805 491 k-4 regular architectures of the 10 14 15-node 30-edge graphs), it is important to distill the optimally learnable graph [49] and to ask whether it has a topology that is common in language or in nature. Is the architecture of the optimally learnable graph also the architecture of a well-written paper or a well-written textbook that effectively communicates networked knowledge to the reader [188]?…”
Section: Pedagogical Principles Conducive To Curious Thoughtmentioning
confidence: 99%
“…The cognitive maps arising from kinesthetic curiosity might improve their learnability, conveying information efficiently by omitting unnecessary detail [62,23,72,73]. Recent work reported that to efficiently convey information, network representations of that information should be characterized by highly connected hubs and tightly linked modules [23,74]. Hubs and modules are features of hierarchical organization exhibited by diverse signatures of kinesthetic curiosity ( Figure 2).…”
Section: Efficient Search Enhances the Learnability Of Cognitive Mapsmentioning
confidence: 99%
“…Yet, due to its emphasis on linking prior knowledge with leaps to new unknowns, the dancer may be the mode of curiosity that best explains the links of curiosity with creativity, learning, and social behavior [103,104,21,105,15,22]. A highly creative person's semantic network displays robustness and hierarchical organization, as does efficient communication [22,21,23,74]. Thus, it would seem natural in future studies of curiosity, creativity, and social behavior to determine whether the dancer, moreso than other modes, builds knowledge networks with greater robustness and more hierarchical organization.…”
Section: The Dancer Creativity Learning and Social Behaviormentioning
confidence: 99%